2018
DOI: 10.1007/s00247-018-4189-6
|View full text |Cite
|
Sign up to set email alerts
|

Lung and airway shape in neuroendocrine cell hyperplasia of infancy

Abstract: Lung and airway shapes were different between children with NEHI and control children in this cohort. Children with NEHI had an increased anteroposterior diameter of their lungs that might be useful in the diagnostic criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Meanwhile, the KEGG and GO analyses of the overlapping genes revealed significant differences among the different tissues (Figures S1 and S2). For example, we found that the heart exhibits tissuespecific regulation of cell cycle function, while the liver exhibits tissue-specific regulation of cell proliferation function, and the lung exhibits tissue-specific regulation of cell shape function [33][34][35]. These findings suggest that different tissues have evolved specialized molecular mechanisms to regulate specific biological functions.…”
Section: Comparison Analysis Of Alternative Splicing Between Duroc An...mentioning
confidence: 77%
“…Meanwhile, the KEGG and GO analyses of the overlapping genes revealed significant differences among the different tissues (Figures S1 and S2). For example, we found that the heart exhibits tissuespecific regulation of cell cycle function, while the liver exhibits tissue-specific regulation of cell proliferation function, and the lung exhibits tissue-specific regulation of cell shape function [33][34][35]. These findings suggest that different tissues have evolved specialized molecular mechanisms to regulate specific biological functions.…”
Section: Comparison Analysis Of Alternative Splicing Between Duroc An...mentioning
confidence: 77%
“…NECs release bombesin, probably involved in the pathogenesis of small airway obstruction [ 29 ]. Mastej et al demonstrated that lung and airway appearances in patients with NEHI presented an increased anteroposterior diameter, suggesting that also this criterion might be considered in the diagnostic criteria [ 30 ]. As demonstrated by Doan et al, the level of serum glycoprotein KL-6 might be a useful biomarker to distinguish NEHI from more severe neonatal surfactant metabolism disorders.…”
Section: Resultsmentioning
confidence: 99%
“…When tested and verified, the automated AAI was able to capture bronchiectasis in cystic fibrosis patients and was positively correlated with expert bronchiectasis scores in different scanners and reconstruction protocols. The automatic bronchiectasis score calculated using this method is a sensitive and objective indicator of research and clinical care [ 6 ].…”
Section: Related Workmentioning
confidence: 99%